Implementation of a broad Accounting Framework of the General Government as a means of reforming the Financial Sector - Zoumi, Aimilia (International Conference on Business and Economics - Hellenic Open University, 2023)
The aim of the present paper is to examine the implementation of the General Accounting Framework of the General Government as a means of reforming the Financial Sector, in relation to all the labyrinthine reforms, which could possibly have taken place before its imposition by the European Union. The implementation of IPSAS is a very important element for global development and prosperity, through the convergence and harmonization of public accounting monitoring systems in different countries and organizations. With the implementation of abroad Accounting Framework of the General Government as a means of reforming the Financial Sector will result in the statements of public sector entities being presented fairly in all respects, with transparency to position and performance of each individual entity and of the government in general and therefore the general public will be aware of the evolution of the government's financial performance. In accordance Government officials will be able to make appropriate decisions if they have timely, complete and reliable information on the actual financial position and financial performance of each public sector entity. JEL classifications codes:Η83,P41, M48